PENANAMAN RASA NASIONALISME MELALUI PEMBELAJARAN SEJARAH PADA SISWA KELAS XI IPS DI SMA NEGERI JATILAWANG - Tiyas Sartika (Khazanah Pendidikan, 2016)
The research was aimed to observe : 1) nationalism values in history subject, 2) the strategiy nationalism values in teaching learning process in history subject, 3) the handicaps done by teacher in improving nationalism sense, 4) the learning outcome in improving nationalism values by history teacher. The research showed that student established nationalism values such as discipline, honesty, diversity, unity, and congruity. Throught speech, discussion, question and answer, also interesting media, relevant sources, motivation and reinforcement to national movement in Indonesia, the teacher was able to estabilish nationalism spirit for the eleventh graders of social class. Keywords : establishment, nationalism, history learning